2018
DOI: 10.1016/j.cherd.2018.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Particle de-agglomeration with an in-line rotor-stator mixer at different solids loadings and viscosities

Abstract: In-line rotor-stators are used in a range of energy intensive processes but there is relatively little published work with these devices on which to base process design. This study was performed to investigate the performance of an in-line rotor-stator for the deagglomeration of nanoparticle clusters in a liquid with the objective of determining the effects of solids loading (up to 15%wt) and continuous phase viscosity (up to 100 mPa•s) on the mechanisms and kinetics of breakup and dispersion fineness. A Silve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…It can therefore be concluded that the characteristic power number values remain constant at Reynolds numbers as low as about 500. Previous work (Padron and Özcan-Taşkın, 2018) with a different rotor-stator had shown this to be the case for Re > 10 3 .…”
Section: Characteristic Power Numbersmentioning
confidence: 71%
“…It can therefore be concluded that the characteristic power number values remain constant at Reynolds numbers as low as about 500. Previous work (Padron and Özcan-Taşkın, 2018) with a different rotor-stator had shown this to be the case for Re > 10 3 .…”
Section: Characteristic Power Numbersmentioning
confidence: 71%
“…The results are in agreement with the literature as similar results on the effect of high-shear mixing on particle disruption have been found in the literature for powders. In particular, Pacek et al ( 2007) [42] and Padron and Özcan-Taskin (2018) [46], found that an in-line high-shear mixer at 8000 rpm, caused the reduction of particles of silicon from 90 µm to 9 µm after 20 min and from 100 µm to 15 µm after 30 min of shearing. The authors have also shown that in the timespan used in the present study (<15 min), in-line highshearing did not allow for the disruption of aggregates below 1-2 µm.…”
Section: Particle Size Distribution and Microstructurementioning
confidence: 99%
“…Buna göre, statordaki delik çapı ve delik sayısının artması ve rotor-stator arasında kalan boşluğun daraltılması topaklaşmayı etkileyici yönde önemli bir etki göstermektedir. Ayrıca ürünlerin karışım hacminde kalma sürelerinin de ürün kalitesini yüksek oranda etkilediği tespit edilmiştir [4] [5] [6].…”
Section: Introductionunclassified